Efficacy and safety outcomes of long-term anti-thrombotic treatment of chronic coronary artery disease: A systematic review and network meta-analysis - Adawi, Nayrouz; Rotshild, Victoria; Yanko, Stav; Mowaswes, Mohammad; Amir, Offer; Haitner, Gal; Matok, Ilan; Raccah, Bruria Hirsh (Frontiers in Cardiovascular Medicine, 2023)
Background: Clopidogrel, prasugrel, ticagrelor, and low-dose rivaroxaban are all optional strategies in conjunction with aspirin for long-term treatment of chronic coronary artery disease. The aim of this research was to assess the efficacy and safety of long-term anti-thrombotic treatment of chronic coronary heart disease. Methods: PubMed (MEDLINE), Embase, Clinical Trials Registry ClinicalTrials.gov, and The Cochrane Library were searched through November 2021, to identify randomized controlled trials that compared long term anti-thrombotic therapy for coronary heart disease. Data were extracted to assess eligibility by two independent reviewers. Random-effects meta-analysis was used to pool results. Results: Eleven randomized controlled trials were included (88,462 patients). In a network meta-analysis, the rivaroxaban compared to the clopidogrel regimen showed lower relative risks (RRs) for death of any cause (0.71; 95% confidence interval [CI], 0.52-0.96), major adverse cardiac events (MACE) (0.73; 95% CI, 0.57-0.93), and cerebrovascular events (0.48; 95% CI, 0.30-0.78). The RR of cerebrovascular events was also lower for the rivaroxaban compared to the ticagrelor 60 mg regimen (0.72; 95% CI, 0.52-0.99). For the prasugrel regimen, the RRs were lower of myocardial infarction incidence versus all extended strategies: clopidogrel plus aspirin (0.76; 95% CI, 0.58-0.99), rivaroxaban (0.60; 95% CI, 0.38-0.93), ticagrelor 60 mg (0.61; 95% CI, 0.42-0.89), and ticagrelor 90 mg (0.63; 95% CI, 0.41-0.97). None of the dual strategies were associated with differences in major bleeding compared to the prasugrel regimen. Conclusions and relevance: The rivaroxaban regimen appeared to be the preferred long-term anti-thrombotic regimen in preventing all-cause mortality. Our available results tend to support the efficacy of extended anti-thrombotic therapy consisting of prasugrel in lowering MI incidence compared to the other strategies, without increased risk of bleeding. However, additional large-scale direct clinical trials are needed to further determine the adequate long-term anti-thrombotic regimens for treating chronic coronary syndrome.